MORALITY DEVIATION IN SAMANTHA DOWNING’S NOVEL MY LOVELY WIFE - Dahlan, Dahlan; Dahlan, Sandra Dewi; Malik, Desi Zalsabilah Kartini (Journal of Islamic Culture and Literature (JICeL), 2023)
The purpose of the research is to explain the morality deviation performed by main characters in Samantha Downing’s Novel My Lovely Wife. This research also aims to find out the factors and consequences of the morality deviation of characters contained in the story. The qualitative descriptive method was used in this research. In collecting the data, the researcher used the Structuralism approach which it revealed the intrinsic elements contained in literary works such as characters, plot, setting, and theme. The results of the research showed that the characters who perform the morality deviation, have a moral decline. Negative behaviors that the characters do, cause morality deviation. Morality deviation does not only bring a bad impact on their own life also the lives of people around them. The consequence that characters got was something that arises from the result of their deeds.